Design and implementation of a standardised framework for the management of a wireless body network in an Mobile Health environment. Issue 3 (15th June 2017) - Talaminos, Alejandro; Naranjo, David; Barbarov, Gerardo; Roa, Laura M.; Reina‐Tosina, Javier
Abstract : The design and implementation of a framework that facilitates the development of Mobile Health applications to manage the communications with biomedical sensors in compliance with the CEN ISO/IEEE 11073 standard family are presented. The framework includes a set of functional modules that are responsible, among other tasks, of the communication of sensors and the processing and storage of data. The mobile terminal acts as an intermediary or hub, collecting and presenting the data received in a standardised way, regardless of the sensor type used. In this context, as proof of concept it is presented a mobile app built on the top of the framework to manage the communications with a smart fall detector.